Cell-permeable mitochondrial ubiquinol–cytochrome c reductase binding protein induces angiogenesis in vitro and in vivo. Issue 1 (28th September 2015) - Chang, Junghwa; Jung, Hye Jin; Park, Hyun-Ji; Cho, Seung-Woo; Lee, Sang-Kyou; Kwon, Ho Jeong
Highlights A novel PTD-UQCRB fusion protein was generated to allow the intracellular delivery of UQCRB. PTD-UQCRB localized to the mitochondria and induced mROS without cytotoxicity. Elevated mROS was sufficient to stabilize HIF-1α, resulting in downstream VEGF expression and angiogenesis in vitro. PTD-UQCRB efficiently enhanced angiogenesis and cutaneous wound healing in vivo. This study indicates that UQCRB engages in angiogenesis and that the novel PTD-UQCRB can be used as a pro-angiogenic agent.